2008
DOI: 10.2478/s11536-008-0016-z
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the interview on pets kept at home for predicting the actual domestic expsoure to their specific allergens. Krakow inner city area study

Abstract: AbstractThe aim of the study was to describe the exposure to dog (Can f 1) and cat (Fel d 1) allergens within homes of very young children living with and without pets, and to assess the validity of the interview on pets for predicting the actual exposure to pet allergens in house dust. House dust samples were collected in 275 dwellings from the mattresses, children’s bedroom and kitchen floors. In the laboratory, dust samples were analyzed for Can f 1 and Fel d 1 using monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Households with pets constitute a significant site of exposure to cat and dog allergens. Similarly to other studies (Ingram et al 1995 ; Raunio et al 1998 ; Fahlbusch et al 2002 ; Arbes et al 2004 ; Jedrychowski et al 2008 ; Nicholas et al 2008 ; Park et al 2014 ), detectable levels of Fel d 1 and Can f 1 were found in almost all homes without pet, but allergen concentrations were significantly lower than in dwellings with pet ownership. Moreover, concentrations of Fel d 1 and Can f 1 were correlated with the number of cats and dogs kept at home.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Households with pets constitute a significant site of exposure to cat and dog allergens. Similarly to other studies (Ingram et al 1995 ; Raunio et al 1998 ; Fahlbusch et al 2002 ; Arbes et al 2004 ; Jedrychowski et al 2008 ; Nicholas et al 2008 ; Park et al 2014 ), detectable levels of Fel d 1 and Can f 1 were found in almost all homes without pet, but allergen concentrations were significantly lower than in dwellings with pet ownership. Moreover, concentrations of Fel d 1 and Can f 1 were correlated with the number of cats and dogs kept at home.…”
Section: Discussionsupporting
confidence: 75%
“…Similar differences in concentration of allergens, depending on the pet ownership and keeping conditions were observed by other authors (Parvaneh et al 1999 ; Nicholas et al 2010 ). Distribution of Fel d 1 and Can f 1 can indicate preferred places of pets staying within the house (Jedrychowski et al 2008 ). As could be expected, the highest concentrations of cat and dog allergens we observed in dust taken from dens of pets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations